Highly emissive nanowires grown from CdTe nanocrystals in a phosphate buffer solution - DONEGAN, JOHN; RAKOVICH, YURY (My University, 2005)
We present details on the CdTe nanowires formation, which were found to grow in a standard physiological phosphate-buffered solution, including in-situ observation of growth with a confocal microscope. The choice of proper nanocrystals concentration allowed reasonably slow growth rates and thus a controllable formation of nanowires. Once formed in solution, nanowires showed a significant degree of structural rigidity and resistance to externally applied mechanical stress. Luminescence and Raman spectroscopy data evidence on re-crystallization processes during the nanowire formation.
Proceedings of SPIE
Opto-Ireland 2005: Nanotechnology and Nanophotonics
PUBLISHED
Dublin
Keywords: In-situ growth; Luminescence; Nanowires; Raman spectroscopy; self-assembly